Processamento do extrato de chá verde (Camellia sinensis) aplicando filtração por membranas - Bindes, Marlon Menezes Maciel (2018)
The consumption of functional beverages and food has increased in the last years mainly due to people concerning about their health and well-being. Camellia sinensis leaves are traditionally used for infusion preparations. Furthermore, considering the high bioactive compounds concentration in its extracts, this herb has been catching the attention of researchers as well as of the food and pharmaceutical industries. Membrane filtration processes may be used for clarification, purification, and concentration of several products. From this point of view, this study focused on the green tea processing, including leaves characterization, extraction, clarification, and purification of polyphenols. In this sense, water was used as a solvent for extraction; macroscopic pre-treatments was applied for clarification (centrifugation and addition of coagulants agent, such as chitosan and Moringa oleífera seeds) and sequentially, a membrane filtration was employed for purification. Initially, the tea was ground, sifted and classified granulometrically. Then, different parameters were evaluated in order to find the best polyphenol extraction condition from tea leaves. The influence of the tea particle was analysed at 80ºC for 30 min for a water-to-tea ratio 50 g L-1 and a tea particle size (0.05-2.83 mm) besides unground leaves. The best tea particle size for polyphenols extraction was 0.15-0.74 mm and it was then used for all further conventional and ultrasound assisted extraction experiments. The optimum ratio was determined by extractions at 80ºC for 30 min with a tea-to-water ratio ranging from 10 to 120 g L-1. The impact of time and temperature on the conventional extraction of polyphenols was evaluated at 50 g L-1 tea-to-water ratio by ranging the time and the temperature from 10 to 120 min and from 40 to 90ºC respectively. Ultrasound-assisted extraction (UAE) consisted of two steps. In the first step of UAE, an experimental design using Response Surface Methodology (RSM) was performed with three replicates at the central point, orthogonality alpha of 1.3531 and at a significance level of 95%. For extraction time of 30 min, temperature, tea-to-water ratio, and amplitude ranged from 22 to 83ºC, 12 to 73 g L-1, 23 to 77% respectively. In the second step of UAE, using the best amplitude determined in step one (77%) and for a water-to-tea ratio 50 g L-1, similarly to conventional extraction, time and temperature varied from 10 to 120 min and from 40 to 90ºC respectively. The optimum extraction condition found in this study was 80ºC, 50 g L-1 for 60 min and a particle size (0.15-0.74 mm). Sequentially, the pre-treatments were performed: centrifugation (8000 rpm, 20 min), chitosan addition (0-2000 mg L-1) and Moringa oleífera seeds addition (0-10.000 mg L-1). Microfiltration processes were carried out at 0.8 bar applying a flat membrane of 0.22 µm and hollow fibres without coating coupled in a home-made cartridge. Microfiltration through hollow fibres without coating presented less polyphenol retention (2.33%), greater solids removal (4.23%), greater turbidity reduction (89.91%) and the greatest steady-state flux (19.37 L h-1m-2) comparatively to flat membrane of 0.22 μm. After the microfiltration processes, a sequential filtration was executed at 1.5 bar employing a home-made cartridge using hollow fibres with a polymeric coating. This sequential process achieved a steady-stead flux of 3.51 L h-1m-2 and a reduction of 9.17% of polyphenols, 12.89% de solids, 80.65% of turbidity and 16.92% of soluble solids (ºbrix). The obtained flux in each filtration process was used to calculate the fouling mechanism and the membrane resistance. In this way, fouling mechanisms (n) and pore resistance values (RP) found for flat membrane of 0.22 µm, hollow fibre without coating and for hollow fibre with coating were internal pore blocking (n=1.5) e (RP = 0.7 x 10-13), cake formation (n=0) e (Rc = 2.80 x 10-13) and intermediary pore blocking (n=1) e (RP = 7.38 x 10-13) respectively. Extract and permeates stability, stored at 5ºC for 30 days, were evaluated using as reference the parameters polyphenols concentration, turbidity and tea cream formation. Only the permeate obtained through filtration by the coated hollow fibre (S5) presented stability (turbidity value less than 4 NTU) and no formation of tea cream during the 30 days of storage at 5ºC. In conclusion, this study found the best polyphenol extraction conditions and proposed the utilisation of centrifugation for clarification followed by filtration through hollow fibres membranes without and with coating for green tea extract purification.